Foundation of libary and information science - Verma, Shiv Ram (Shree, 2005)
Contents of material: Library as a social institution. Socio-historical analysis of library and information science. Library and information profession. Public libraries. Role of libraries in education. Resources sharing and networking. Development of libraries. Global digital libraries.